Analisis Pengaruh Pembiayaan Murabahah Pada Bank Umum Syariah Di Indonesia (Periode Januari 2011 - Juni 2015) - Rizkhi Hidayati, Ika; , Ir. MS, Maulidyah Indira Hasmarini (2016)
This study aimed to test whether a variable Third Party Fund (DPK), Non Performing Financing (NPF), and Financing to Deposit Ratio (FDR) affect the financing murabaha of the Islamic Bank in Indonesia with the object of research that Islamic Banks (BUS) in Indonesia using secondary data based on the monthly time series January 2010- june 2015. The analysis technique used is the Model of error correction model to the significance (α) of 0.05. The results of this study indicate that DPK had a negative and significant impact on the financing murabaha of Bank Syariah, NPF and FDR has a positif and significant impact on the financing murabaha of Bank Syariah, in the long term DPK, NPF, and FDR positive influence and jointly significant effect on financing in Islamic Banking in Indonesia in the period January 2011- june 2015. Keywords: financing murabaha, Third Party Fund (DPK), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR).